Model Test and Numerical Simulation Study on the Effect of Mudcake and Length-Diameter Ratio on the Bearing Capacity of Bored Cast-in-Place Piles - Peisheng Xi; Mengxuan Kan; Yang Liu (Advances in Civil Engineering)
To study the effect of length-diameter ratio and mudcake on the bearing capacity of bored cast-in-place piles, the indoor model test and finite element numerical simulation method were used to carry out the loading test of piles under different mudcake thicknesses (0 and 0.5 mm) and different length-diameter ratios (10, 14, and 24). The variation law of pile top displacement, pile bearing capacity, pile axial force, and lateral friction resistance under the vertical load was analyzed. The results show that the larger the length-diameter ratio of bored pile is, the more effectively the negative influence of mudcake around the pile on the settlement and end resistance of the pile is restrained, and the ultimate bearing capacity of the pile is improved. The research results have important scientific value and practical significance for understanding the influence of length-diameter ratio on bearing capacity of bored cast-in-place piles.